A Real-World Safety Profile in Neurological, Skin, and Sexual Disorders of Anti-Seizure Medications Using the Pharmacovigilance Database of the Korea Adverse Event Reporting System (KAERS) - Kim, Dajeong; Lee, Sukhyang (Journal of Clinical Medicine, 2024)
(1) Background: The utilization of high-quality evidence regarding the safety of anti-seizure medications (ASMs) is constrained by the absence of standardized reporting. This study aims to examine the safety profile of ASMs using real-world data. (2) Methods: The data were collected from the Korea Adverse Event Reporting System Database (KAERS-DB) between 2012 and 2021. In total, 46,963 adverse drug reaction (ADR)–drug pairs were analyzed. (3) Results: At the system organ class level, the most frequently reported classes for sodium channel blockers (SCBs) were skin (37.9%), neurological (16.7%), and psychiatric disorders (9.7%). For non-SCBs, these were neurological (31.2%), gastrointestinal (22.0%), and psychiatric disorders (18.2%). The most common ADRs induced by SCBs were rash (17.8%), pruritus (8.2%), and dizziness (6.7%). Non-SCBs were associated with dizziness (23.7%), somnolence (13.0%), and nausea (6.3%). Rash, pruritus, and urticaria occurred, on average, two days later with SCBs compared to non-SCBs. Sexual/reproductive disorders were reported at a frequency of 0.23%. SCBs were reported as the cause more frequently than non-SCBs (59.8% vs. 40.2%, Fisher’s exact test, p < 0.0001). (4) Conclusions: Based on real-world data, the safety profiles of ASMs were identified. The ADRs induced by SCBs exhibited different patterns when compared to those induced by non-SCBs.
Keywords: adverse event reporting system; adverse reproductive outcome; anti-seizure medication; epilepsy; Korea Adverse Event Reporting System Database (KAERS DB); pharmacovigilance; sodium channel blockers